The British Association for Sexual Health and HIV 2016 UK national audit and survey of clinic policies in relation to risk assessment, HIV testing and follow-up. (October 2018) - Bhaduri, S; Curtis, H; McClean, H; Sullivan, AK; ,
This national audit of 142 clinics demonstrated that the majority of clinics surveyed had policies and agreed clinical practice for alcohol and recreational drug enquiry, as well as documentation of HIV test refusal, although this was not the case in 24% of clinics as regards alcohol usage, 21% of clinics as regards recreational drugs use and 43% of clinics as regards chemsex usage. Regarding management of HIV test refusal, there was no policy or agreed practice in 13% of clinics with respect to men having sex with men (MSM) attenders, and in 18% of clinics for heterosexual attenders. Seventy percent of clinics had HIV point of care tests (POCT) available. Recommendations include: all clinics should have a policy of routine enquiry about alcohol, recreational drugs and chemsex, all clinics should record reasons for HIV test refusal and all clinics should provide testing alternatives to improve uptake, e.g. point of care testing or home sampling.